A ratiometric electrochemical microsensor for monitoring chloride ions in vivo. Issue 20 (14th September 2021) - Xiao, Xia; Li, Chenchen; Liu, Yuzhi; Feng, Yaqian; Han, Kai; Xiang, Haoyue; Shi, Guoyue; Gu, Hui
Abstract : Chloride ion (Cl − ), the most common anion in animal brain, has been verified to play a vital role in maintaining normal physiological processes. Abstract : Chloride ion (Cl − ), the most common anion in animal brain, has been verified to play a vital role in maintaining normal physiological processes. Thus, development of a reliable platform to determine Cl − is of great significance for brain research involving Cl − . In this work, a ratiometric electrochemical microsensor (REM) for the in vivo measurement of cerebral Cl − was designed. To prepare REM, uniform Ag nanoparticles (Ag NPs) with nano-level sizes were synthesized via an adsorption–reduction process, which served as selective recognition elements for Cl − determination, while methylene blue (MB) was absorbed and acted as an inner reference unit to avoid the environmental interference of complicated brain systems. As a result, this developed REM exhibited high sensitivity and selectivity, as well as good stability, reproducibility and anti-biofouling. This reliable approach was established to monitor Cl − in mouse brain.